Ensayo no aleatorizado de una intervención educativa basada en principios cognitivo-conductuales para pacientes con lumbalgia crónica inespecífica atendidos en fisioterapia de atención primaria() - Díaz-Cerrillo, Juan Luis (Aten Primaria, 2016)
OBJECTIVE: To assess the influence of an educational intervention in reducing «fear-avoidance» (FA) and «pain catastrophising» (CAT) in a population with unspecific chronic low back pain (UCLBP), attending physiotherapy in Primary Health Care. A pragmatic quasi-experimental study was conducted in Health Centres of a Costa del Sol Health District. DESIGN: Quasi-experimental study. SETTING: Primary Health Care physiotherapy Back Schools in Health Centres of a Costa del Sol Health District. PARTICIPANTS: The selection criteria were: UCLBP; 18-65 years; understanding of the Spanish language; absence of parallel educational interventions; absence of red flags; not showing cognitive impairment or fibromyalgia; absence of thoracic-lumbar surgery, and exercise tolerance. INTERVENTIONS: The control group received the usual Back Schools program. The experimental group also received a written document for home reading, plus the subsequent sharing, clarifying doubts, and beliefs and goals restructuring during the development of the sessions. Both interventions lasted about 280 minutes (7 sessions × 40 min). RESULTS: The main variables included FA and CAT. Pain and disability were also assessed. Some «demographic» and «related disorder» variables were considered in the analysis. Statistically significant differences were observed in the experimental group versus control, in the variation of FA −14 (−25.5; 0) vs −4 (−13; 0) (P = .009), and CAT −9 (−18; −4) vs −4,5 (−8.25; 0) (P = .000), were observed. Also differences in disability (P = .046), but not in pain (P = .280). CONCLUSIONS: These results should be considered in light of possible limits imposed by the study. Its pragmatic nature would allow a potential transfer to usual care.